The health benefits of bicycling to school among adolescents in China: A propensity score matching study - Ding, Pengxiang; Ding, Chang; Feng, Suwei (Frontiers in Public Health, 2023)
Background A large number of high-income countries are now promoting active commuting to school as an opportunity for adolescents to increase physical activity (PA) and improve their health. Few studies have examined the multiple benefits of active travel to school among adolescents in developing countries, especially in China. Hence, this study aims to estimate the effects of bicycling to school on adolescents’ subjective health, physical health, and sickness absence. Methods Self-reported and cross-sectional data from 6,353 school-aged children (12–19 years old) in the 2014–2015 China Education Panel Survey (CEPS2014-2015) were used. The independent variable was a binary, self-reported indicator of whether children bicycled to school. The dependent variables included subjective health (self-reported health, mental stress), physical health (BMI, kidney disease, lung disease, heart disease, brain disease, upper limb fracture, lower limb fracture, and sickness frequency), and sickness absence. Propensity score matching (PSM) was used to estimate the causal effects of bicycling to school on adolescents’ health. Results Bicycling to school positively affects both subjective and physical health. Those students who biked to school were associated with a higher self-rated health status, a healthier weight, a lower level of mental stress, and a lower risk of developing brain diseases. No significant relation is found between bicycling and sickness frequency, and sickness absence. Moreover, we separately compared the bicycling group with the walking group and the non-active travel group. There is still evidence that cycling is beneficial for students. Compared with walking to school, cycling to school resulted in a higher self-rated health score and a lower mental stress score. Physically, students who bicycled to school were less likely to be absent from school and suffer from kidney and brain diseases than students who walked to school. However, we do not find a significant difference in health outcomes from cycling compared to non-active modes of transportation. Further, differentiation of the health effects of bicycling across living areas shows that health effects are more pronounced for those living in edge and rural areas. Conclusion These findings provide evidence of the value of promoting bicycling to school in improving various adolescents’ health outcomes in transitional China.